Effectiveness of the Combination of Facial Acupressure and Honey on Facial Skin Moisture - Ayly Soekanto; Putu Oky Ari Tania; Andra Agnez Al Aska; Hardiyono Hardiyono (Universitas Wijaya Kusuma Surabaya, 2024)
Background: Facial skin is the most sensitive part, so it is important to take care of it. Facial skin care is a treatment to keep facial skin elastic and maintain facial skin moisture. Facial acupressure is a method of treatment that begins with massaging the meridian points so that blood flow becomes smooth and facial muscles feel more relaxed. Using honey is a facial skin care method that is made into a mask. Objective: The research aims to determine the effectiveness of the combination of facial acupressure and honey on facial skin moisture. Methods: This research is an analytical experimental study, with a sample of 30 women aged 40 - 50 years. In the first treatment, a moisture test was carried out, followed by the second treatment, the moisture test was measured for the facial acupressure and after the third treatment, the combination of the facial acupressure with a honey mask was subjected to a moisture test. The research was carried out twice a week for 4 weeks for a total of 8 times. The research was carried out in April – May 2024 at the Wijaya Surabaya clinic & in a doctor's practice and used a Skin Moisture Analyzer as a measuring tool to measure skin moisture. Using statistical analysis with the Mann-Whitney test (α= 0.05) with a p-value of 0.000. Result: The results of the third treatment showed an increase in facial skin moisture until it reached 93.4%, including moist skin and 6.6%, which was considered normal skin criteria. Conclusion: It has been proven that the combination of facial acupressure and honey is effective on facial skin moisture, experiencing very significant changes in humidity starting from the first, second and third treatments.